Pengaruh Implementasi Program Qlue dan Komitmen Organisasi Terhadap Efektivitas Pelayanan Publik di Pemerintah Provinsi DKI Jakarta Tahun 2015-2018 - Lijan Poltak Sinambela; Rusman Ghazali; Senja Diana Rosai (Populis : Jurnal Sosial dan Humaniora, 2023)
Community service can be categorized as effective if the community gets the ease of service with a short, fast, precise and satisfying procedure. The success of increasing the effectiveness of public services is determined by various variables, including the variable of the government's ability to increase the organizational commitment of government officials. Especially for the government of the Special Capital Region of Jakarta, the demands of the community for the convenience of public services are increasingly emerging. The DKI Jakarta government has responded to this by developing various information technologies through various programs, one of which is the QLUE program. This program is expected to provide convenience in making public complaints, so that service effectiveness can be increased. In order for this program to be accepted and to solve various community problems, the DKI Provincial Government is collaborating with various parties and adding a variety of channels for public complaints. This inspired the writer to research the effectiveness of public services in DKI Jakarta. The results of this study indicate that the implementation of the QLUE program and organizational commitment amounted to 89.0% of the effectiveness of public services in the DKI Jakarta Provincial Government. Partially test that indicators of work motivation and work performance have a dominant influence.  Pelayanan masyarakat dapat dikategorikan efektif apabila masyarakat mendapatkan kemudahan pelayanan dengan prosedur yang singkat, cepat, tepat dan memuaskan. Keberhasilan meningkatkan efektivitas pelayanan publik ditentukan berbagai peubah, di antaranya peubah kemampuan pemerintah dalam meningkatkan komitmen organisasi aparat pemerintah. Terlebih bagi pemerintahan Daerah Khusus Ibu Kota Jakarta, tuntutan masyarakat memperoleh kemudahan pelayanan publik semakin mengemuka. Hal ini pun direspon pemerintah DKI Jakarta dengan mengembangkan berbagai teknologi informasi melalui berbagai program, di antaranya adalah program QLUE. Program ini diharapkan dapat memberikan kemudahan dalam melakukan pengaduan publik, sehingga efektivitas pelayanan dapat ditingkatkan. Agar program ini dapat diterima dan menyelesaikan berbagai masalah masyarakat, Pemprov DKI melakukan kerjasama dengan berbagai pihak dan menambah variasi kanal untuk pengaduan publik. Hal itu menginspirasi penulis untuk meneliti efektivitas pelayanan publik di DKI Jakarta. Hasil penelitian ini menunjukkan bahwa implementasi program QLUE dan komitmen organisasi sebesar 89,0% terhadap efektivitas pelayanan publik di pemerintah Provinsi DKI Jakarta. Uji secara parsial bahwa indikator motivasi kerja dan prestasi kerja memberikan pengaruh dominan